2019
DOI: 10.1016/j.foodhyd.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Functionalisation of pea protein by tryptic hydrolysis – Characterisation of interfacial and functional properties

Abstract: With regard to applications in dispersed systems (i.e. emulsions), improving the poor solubility of pea protein in the pH-range applicable to foods (pH 3 to pH 7) is a prerequisite. To achieve this, a pea protein concentrate was produced on a lab scale using alkaline extraction and subsequent enzymatic hydrolysis to degrees of 2 and 4%. Solubility was improved and interfacial properties were influenced. All samples led to the formation of emulsions but displayed a tendency towards wider oil-droplet size distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…However, on day 3, a decrease in ζ-potential of 2 and 8 mV was observed for A and E, respectively. Similar values were founded by Klost & Drusch [48] for O/W emulsions at pH 3. They detected a ζ-potential of 30 mV for pea extracted with an alkaline method.…”
Section: ζ-Potential and Hydrodynamic Diametersupporting
confidence: 89%
“…However, on day 3, a decrease in ζ-potential of 2 and 8 mV was observed for A and E, respectively. Similar values were founded by Klost & Drusch [48] for O/W emulsions at pH 3. They detected a ζ-potential of 30 mV for pea extracted with an alkaline method.…”
Section: ζ-Potential and Hydrodynamic Diametersupporting
confidence: 89%
“…Pea protein was produced on lab scale as previously described in more detail (Klost & Drusch, 2019). Briefly, dry peas were ground and the flour was dispersed in 0.0375 M NaOH leading to an initial pH value of approximately 8.7 which dropped to just above pH 8 during the extraction time.…”
Section: Methodsmentioning
confidence: 99%
“…When rapeseed oil was added to the samples, the oil was emulsified by the protein during the homogenisation step before fermentation. From a previous study (Klost & Drusch, 2019) we know that a protein content of 1% is sufficient to stabilise 5% rapeseed oil. Samples in the current study contained 10% protein and 4% oil, leading to sufficient bulk protein for network formation.…”
Section: Samplementioning
confidence: 99%
“…Figure 1B demonstrates that the 23, 33 and 34 kDa proteins are the main components of Po SMP, followed by 38 and 49 kDa proteins. The 34 kDa band with the highest protein content was conveniently hydrolysed by alcalase and pepsin, which suggested that the band may have a large number of amino acids at the two enzyme cleavage sites or related to the hydrolysis condition [30]. In contrast, proteins at 23 and 38 kDa showed strong resistance to most of the selected enzymes, and only pepsin could hydrolyse under acidic conditions, which may be related to the spatial structure and special functions of the proteins [31].…”
Section: Resultsmentioning
confidence: 99%